Comparative Pharmacological Potential of Cumin (Cuminum cyminum) Seed Essential Oils: Conventional vs. Superheated Steam Distillation: Pharmacological potential of cumin seed oils: Superheated steam vs. conventional extraction techniques - Anjam, Muhammad; Ayub, Muhammad; Altaf , Hafiza; Saeed, Alina; Shahid , Muhammad; Jilani, Muhammad (Iranian Journal of Pharmaceutical Sciences, 2025)
Cuminum cyminum is a famous spice used worldwide for imparting taste to diverse food provisions, culinary and medicinal purposes, and also for appetizing purposes due to its special aromatic effect. This research work aims to estimate the yield of essential oil (EO), chemical composition, antioxidant and antimicrobial activity of Cuminum cyminum EOs extracted by conventional methods Hydrodistillation (HD) and Steam distillation (SD) towards advanced method Superheated steam distillation (SHSD). SHSD noticed the maximum EO yield compared to the HD and SD methods. Gas chromatography-mass spectrometry (GC-MS) analysis illustrated that Cumin aldehyde (51.87-23.54%) and 3-caren-10-ol (15.34-12.15%) were the most abundant compounds of Cuminum cyminum EOs. Hydrogen peroxide scavenging, ferric-reducing power assay, and DPPH free radical scavenging assay were used to evaluate the antioxidant potential. Results revealed that SHSD EO displayed the highest antioxidant potential compared to HD and SD EOs. The antimicrobial activity was determined using the resazurin microtiter plates test, microdilution broth experiment, and disc diffusion tests contradicting food pathogenic bacterial and fungal strains. SHSD EO observed the highest antimicrobial potential. The results indicated that SHSD is an efficient and excellent method for extracting EOs from Cuminum cyminum seeds, which also engage in biological activities.